Low-Field Magnetic Resonance Imaging: Its History and Renaissance. Issue 11 (November 2021) - Hori, Masaaki; Hagiwara, Akifumi; Goto, Masami; Wada, Akihiko; Aoki, Shigeki
Abstract : Abstract: Low-field magnetic resonance imaging (MRI) systems have seen a renaissance recently due to improvements in technology (both hardware and software). Originally, the performance of low-field MRI systems was rated lower than their actual clinical usefulness, and they were viewed as low-cost but poorly performing systems. However, various applications similar to high-field MRI systems (1.5 T and 3 T) have gradually become possible, culminating with high-performance low-field MRI systems and their adaptations now being proposed that have unique advantages over high-field MRI systems in various aspects. This review article describes the physical characteristics of low-field MRI systems and presents both their advantages and disadvantages for clinical use (past to present), along with their cutting-edge clinical applications.